Investigation of Gadobutrol-Induced Sister Chromatid Exchange in G0 Phase and Circulating Human Lymphocytes - Hayal, Cobanoglu; Cayir, Akin (Archives of Pharmacy, 2025)
Gadobutrol (Gadovist®) is a macrocyclic, extracellular gadolinium-based contrast agent widely used in magnetic resonance imaging. This study aims to assess the genotoxic and cytotoxic potential of gadobutrol in human G0 phase lymphocytes and circulating lymphocytes. The Sister Chromatid Exchange (SCE) assay, a fast, sensitive, and reliable method for evaluating genotoxicity, was employed. Genotoxic effects were assessed by measuring SCE frequency, while cytotoxicity was determined using the mitotic index (MI). Peripheral blood samples from two healthy donors were treated in vitro with three different concentrations of gadobutrol for 24 hours in G0 phase lymphocytes and 72 hours in circulating lymphocytes. The results indicated that gadobutrol did not exhibit cytotoxic effects in either cell type. However, at the highest concentration (25 mM), gadobutrol significantly increased the formation of SCE in circulating lymphocytes (p < 0.05), while no significant genotoxic effect was observed in G0 phase lymphocytes (p > 0.05). These findings suggest that gadobutrol, although not cytotoxic, may induce genotoxic effects in a concentration-dependent manner in circulating lymphocytes. Further studies are needed to explore the clinical implications of these findings.